A new species of Batesimalva (Malvaceae) from Coahuila, Mexico - Villareal-Quintanilla, José A.; Fryxell, P.A. (Instituto de Ecología, A.C., 1990)
A new species of Batesimalva (Malvaceae) is described from the southwestern part of the State of Coahuila. It differs from the known species in its palmately parted leaves, longer stipules, deeply divided calyx and its smaller height. An illustration is included.